1992
DOI: 10.1111/j.1365-2133.1992.tb00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Scarring alopecia in discoid lupus erythematosus

Abstract: The clinicopathological features of the scarring alopecia of discoid lupus erythematosus (DLE) were studied. Scarring alopecia was present in 34% of 89 patients with DLE and was associated with a prolonged disease course. More than half these patients had scalp involvement at the onset of the disease. There was a significant reduction in size of sebaceous glands in affected scalp. Perifollicular lymphocytic inflammation was maximal around the mid-follicle at the level of the sebaceous gland, which seems to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 25 publications
3
74
0
1
Order By: Relevance
“…In our study, commonest histopathological feature of alopecia was perifollicular fibrosis seen in 65% patients,basal cell vacuolization was seen in 52.5% patients,perifollicular lymphocytic infiltrate were seen in 50% patients, epidermal atrophy seen in 35% patients and hyperkeratosis was seen in 20% patients. The combination of diffuse scaling, erythema, telangiectases, and mottled hyperpigmentation within areas of scarring alopecia was a distinctive feature of DLE [6,7]. In most patients with LP, the histologic changes involved only the follicles and the perifollicular dermis.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, commonest histopathological feature of alopecia was perifollicular fibrosis seen in 65% patients,basal cell vacuolization was seen in 52.5% patients,perifollicular lymphocytic infiltrate were seen in 50% patients, epidermal atrophy seen in 35% patients and hyperkeratosis was seen in 20% patients. The combination of diffuse scaling, erythema, telangiectases, and mottled hyperpigmentation within areas of scarring alopecia was a distinctive feature of DLE [6,7]. In most patients with LP, the histologic changes involved only the follicles and the perifollicular dermis.…”
Section: Discussionmentioning
confidence: 99%
“…CCLE of the scalp may precede, coexist, or follow other skin lesions. 6 In an earlier study by Wilson et al,4 34% of patients with CCLE had scalp involvement and this may serve as a marker of chronicity and poor response to treatment. In a smaller study by Callen, 7 41% of patients with CCLE had cicatricial alopecia.…”
Section: Lymphocytic Cicatricial Alopeciasmentioning
confidence: 98%
“…In accordance with previous studies, we observed a female predominance of lymphocytic cicatricial alopecias. [2][3][4] In our series, both LPP and CCLE affected predominately middle-aged adults, although LPP appears to have a later onset in life. In lupus erythematosus, the activity of the disease is primarily focused in the center of the plaque, whereas in LPP the activity predominately occurred at the periphery.…”
Section: Lymphocytic Cicatricial Alopeciasmentioning
confidence: 99%
“…4,6---9 Moreover, atrophy and destruction of the sebaceous glands are often observed from early stages. 7,9 In the late stages, CCLE lesions show striking lamellar fibrosis, surrounding the upper follicle, although these lesions can also be panfollicular, and as the condition progresses, the follicle may be completely destroyed ( Fig. 1).…”
Section: Chronic Cutaneous/discoid Lupus Erythematosusmentioning
confidence: 96%